A point of view about forms and compositions in interior design through the optics of art (Revista de Ensino em Artes, Moda e Design, 2021)
This article has the objective to communicate a postgraduate monograph, which is an analysis of the book Art Universes by Fayga Ostrower and it’s relationship with interior design. In order to do so, the experiment shown in the book was used as the basis, in which the author discusses the classes she taught to factory workers some concepts of composition and form in order to help them understand artworks. At first, research contextualizes how this experiment was made and what are these concepts about, to then demonstrate its applicability in interior design. This can be noticed through the analysis made between the correlation of the architect and designer Patricia Urquiola's projects with the application from the central point of view of the theme.
Keywords: Fayga Ostrower; Gestalt; Interior design; Patricia Urquiola